Preparation and Characterization of Cobalt Aluminate Spinels CoAlO Doped with Magnesium Oxide - Christine Azer; Adham R. Ramadan; Gehane Ghaly; Jehane Ragai (Adsorption Science & Technology)
Cobalt aluminate spinels were prepared from cobalt and aluminium nitrate solutions using sol–gel synthesis route by ammonium hydroxide precipitation. The gels were dried at 75°C, doped with different amounts of magnesium nitrate, and then calcined for 3 h at 650°C. Sample characterization was carried out by infrared spectroscopy, X-ray diffraction, scanning electron microscopy, nitrogen adsorption studies, thermogravimetry and by determining acid–base properties. This was carried out with the objective of elucidating the effect, if any, of the presence of the dopant on the spinel structure and properties. The spinel structure was clearly exhibited in all of the prepared samples which were predominantly mesoporous. None of the samples showed any acidic properties, i.e. they exhibited only basic properties. We found that doping with Mg resulted in a slightly increased disorder of cation distribution for those samples doped with higher amounts of Mg. Doping also led to a general increase in surface areas and the development of larger pores, as well as larger content of chemisorbed water.